Discretionary Powers in the Context of Legal Regulation of Administrative Procedure - Luk’yanets, Dmytro (Problems of legality, 2023)
The article is devoted to the problem consideration of determining the content and characteristics of discretionary powers in the context of the administrative procedure legal regulation, which is caused by the adoption and necessity of introducing the provisions of the Law of Ukraine «On Administrative Procedure» into the practices of the subjects of authority. The actuality of the topic is determined by the necessity to qualify administrative bodies' powers as discretionary and implement the relevant principles of administrative procedure. The article aims to analyze the normative constructions of administrative proceedings available in Ukraine's legislation, which allow for the possibility of exercising discretionary or similar powers to develop a position regarding the limits and features of the practical application of norms of the Law of Ukraine «On Administrative Procedure». Achieving the outlined objective became possible through complex scientific knowledge methods, in particular dialectical and systemic approaches, formal-legal and comparative methods, and methods of analysis and synthesis. It is noted that the vast majority of normatively defined principles of administrative procedure are designed for the implementation of discretionary powers by administrative bodies. It was emphasized that an integral component of discretionary powers, in addition to the availability of legally defined options for decisions that an administrative body can adopt in the presence of specific grounds, is the availability of the administrative body's right to act at its discretion. Based on the conducted research on the content of the administrative bodies' powers in specific types of administrative proceedings, the conclusions were formulated that in administrative proceedings of a registration and permitting nature, the relevant administrative bodies do not have discretionary powers. It is noted that an example of full-fledged discretionary powers is the powers of administrative bodies in tort proceedings. This is due to the fact that sanctions for the commission of relevant offenses have a relatively defined nature. In such cases, the administrative body, at its discretion, selects the type and amount of sanctions, taking into account the circumstances of the case. Unlimited discretion is inherent in the authority of collegial bodies, particularly local self-government bodies, which is determined by the decision-making method by voting of the collegial body members.